Foundations of Computational Mathematics 1997
DOI: 10.1007/978-3-642-60539-0_12
|View full text |Cite
|
Sign up to set email alerts
|

On the Qualitative Properties of Modified Equations

Abstract: Suppose that a consistent one-step numerical method of order r is applied to a smooth system of ordinary differential equations. Given any integer m 1, the method may be shown to be of order r + m as an approximation to a certain modi"ed equation. If the method and the system have a particular qualitative property then it is important to determine whether the modi"ed equations inherit this property. In this article, a technique is introduced for proving that the modi"ed equations inherit qualitative properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
(19 reference statements)
1
6
0
Order By: Relevance
“…, ∞, possess F as a first integral. The same result was recently derived by Gonzalez, Higham, and Stuart [13] using a contradiction argument. Example 2.…”
Section: Geometric Propertiessupporting
confidence: 85%
See 2 more Smart Citations
“…, ∞, possess F as a first integral. The same result was recently derived by Gonzalez, Higham, and Stuart [13] using a contradiction argument. Example 2.…”
Section: Geometric Propertiessupporting
confidence: 85%
“…In section 3, it will be shown that this leads to a simple characterization of the geometric properties of the modified vector fields and, in section 4, explicit estimates for the difference between the time-one-flow map of the modified vector field X i (δt) and the numerical method will be given. We like to point out that these results can also be (and have been [16,5,18,20,13]) derived using an explicit Taylor series expansion of the flow map and the numerical method. However, we feel that the application of the recursion (2.4)-(2.5) leads to a simplification in the presentation of these results.…”
Section: The Modified Vector Field Recursion Let Us Consider a Smootmentioning
confidence: 71%
See 1 more Smart Citation
“…Backward error analysis asks that the computed solution be the solution to a nearby problem and considers a slightly perturbed problem with the same initial conditions. This idea is related to the concept of modified equations [19]. The third type of error analysis, the type with which we concern ourselves, is shadowing.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although the orbit of a planet may be reproduced correctly by the numerical trajectory, the time at which a real and simulated planet pass through a fixed plane perpendicular to the orbit may differ. This is the case even if the integrator is symplectic Gonzalez and Stuart 1996). Thus, when attempting to shadow a numerical solution of an ODE, it may be necessary to "rescale" time (Coomes, Koçak, and Palmer 1994b, 1995a, 1995bVan Vleck 1995).…”
Section: Introductionmentioning
confidence: 99%